Focus Issue: Neck Dissection for Oropharyngeal Squamous Cell Carcinoma - Van Abel, Kathryn M. (International Scholarly Research Network, 2012)
The staging and prognosis of oropharyngeal squamous cell carcinoma is intimately tied to the status of the cervical lymph nodes. Due to the high risk for occult nodal disease, most clinicians recommend treating the neck for these primary tumors. While there are many modalities available, surgical resection of nodal disease offers both a therapeutic and a diagnostic intervention. We review the relevant anatomy, nodal drainage patterns, clinical workup, surgical management and common complications associated with neck dissection for oropharyngeal squamous cell carcinoma.